Novel UHF RFID Near-Field Reader Antenna with Uniform Vertical Electric Field Distribution - Yanbin Chen; Xiaojuan Ren; Jimin Zhao; Xin Chen; Yuan Yao; Junsheng Yu; Xiaodong Chen (International Journal of Antennas and Propagation)
This paper presents two novel UHF RFID near-field reader antennas with uniform vertical electric field distribution. The two antennas have the following common characteristics. First, the radiating parts of the two antennas are simulated and fabricated by the microstrip lines and work using the leakage wave principle of microstrip lines. Second, the end of microstrip lines match the load to form a traveling wave mode of operation, so the two antennas have broadband characteristics. Third, both antennas are fed in a coaxial manner at the center of the antenna. The simulation and measurement results can show that the proposed three-branch antenna and four-branch antenna achieve good impedance matching in the range of 883–960 MHz and 870–960 MHz, respectively, and achieve uniform distribution of the vertical electric field component in a certain area. The reading areas of the three-branch antenna and the four-branch antenna are 70 mm × 70 mm × 90 mm and 100 mm × 100 mm × 120 mm (length × width × height), respectively. Due to the introduction of the ground plate, the antenna gain is low, which meets the design requirements of near-field antennas.